Synthesis of ultraluminescent gold core–shell nanoparticles as nanoimaging platforms for biosensing applications based on metal-enhanced fluorescence. Issue 17 (6th February 2017) - Gontero, D.; Veglia, A. V.; Bracamonte, A. G.; Boudreau, D.
Abstract : Core–shell nanoparticles are versatile nanostructures that can be applied as luminescent biosensing platforms in many nanotechnological developments. Abstract : Core–shell nanoparticles are versatile nanostructures that can be used as luminescent biosensing platforms in many nanotechnological developments. Ultraluminescent fluorescent gold core–shell nanoparticles based on Metal-Enhanced Fluorescence (MEF) were synthesized. The nanoparticles obtained were formed by 40.0 nm cores and variable silica spacer lengths. Silica spacer lengths from 6.0 to 25.0 nm were obtained. The plasmon maximal wavelength of the core–shell nanoparticles was shifted to a longer wavelength from a gold nanoparticle plasmon centered at 537.0 nm to 545.0 nm and 548 nm from 6.0 nm to 20.0 nm spacer length, respectively. The effect of the gold core on emission was evaluated by determination of Metal Enhanced Fluorescence enhancement factors (MEFEF ), applying the sodium cyanide method for core leaching. We observed maximal MEFEF = 8.1 and 7.2 for 6.0 and 14.0 nm, respectively, and a significant decrease at longer silica spacer lengths. From nanoimaging by confocal fluorescence microscopy it was possible to detect ultraluminescent gold core–shell nanoparticle aggregates and obtain an MEFEF that can rise to 40. These parameters and properties were discussed from the point of view of fluorescent platform applications. Moreover in order to show the potential application of these nanoparticles in biodetection and nanomedicine, Escherichia coli bacteria were labelled with ultraluminescent nanoparticles. Bright and clear bacteria images were obtained by laser fluorescence microscopy. Based on these results, future applications for individual bacterial detection will be developed.